Why do Indonesian Islamic Banks Take the Risk?: The Case of Two Major Islamic Banks - Azinuddin, Ar Rizal; Syamlan, Yaser Taufik (Universitas Muhammadiyah Yogyakarta, 2019)
This study aims to analyze the effect of bank size, deposit guarantee system, number of competitors, leverage, and bank age on the risk-takingbehavior of Islamic banks in Indonesia at the period of 2001-2016. Risk taking is projected to Financing to Asset Ratio (FAR). The deposit guarantee system is proxiedby deposit guarantee using a dummy variable. The number of competitors is proxiedby the market value of Islamic Banking. Leverage is proxiedbythe total of third party funds. Bank Age is proxiedby bank age according to the 2001-2016 period of study. This study uses secondary data from published financial reports and uses panel data regression methods. The samples are two pioneers of Islamic Bank in Indonesia, namely Bank Muamalat Indonesia and Bank SyariahMandiri. The results of this study show that Bank Size has a positive effect on risk taking. As a result also applies to the number of competitors and Bank Age. Only Deposit Insurance variable that has a positive but not significant influence and Leverage variable has the significant negative effect. In conclusions, the Islamicbank takes the risk due to the tight competition, the age of bank, the amount of third party fund collected and the asset of the bank.